2016
DOI: 10.1016/j.ridd.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The written expression abilities of adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Students with Attention-Deficit/Hyperactivity Disorder (ADHD) often experience deficits in academic achievement. Written expression abilities in this population have not been extensively studied but existing prevalence estimates suggest that rates of comorbid writing underachievement may be substantially higher than rates of comorbid reading and mathematics underachievement. The current study examined written expression abilities in a school-based sample of 326 middle school age students with ADHD. The prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…However, improved visual motor integration in adolescents with ADHD would only increase readability of Chinese handwriting. This suggests that Chinese and English are two fundamentally different languages such that the former heavily relies on orthographic and logographic structures (Wang & Geva, 2003) whereas the latter is highly related to sound–letter correspondences (Molitor, Langberg, & Evans, ). Such discrepancy may contribute to the difference in the influence from sensorimotor performance to English and Chinese handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…However, improved visual motor integration in adolescents with ADHD would only increase readability of Chinese handwriting. This suggests that Chinese and English are two fundamentally different languages such that the former heavily relies on orthographic and logographic structures (Wang & Geva, 2003) whereas the latter is highly related to sound–letter correspondences (Molitor, Langberg, & Evans, ). Such discrepancy may contribute to the difference in the influence from sensorimotor performance to English and Chinese handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation may relate to the nature of the Digit Span Backwards task. More specifically, some researchers have argued that although it is frequently used as a measure of working memory, it is relatively shallow in its processing demands (e.g., St Clair-Thompson, 2010 ; Georgiou and Das, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Writing seems to be the most impaired and the least studied skill in this group of children (Mayes & Calhoun, 2006;Dorneles et al, 2014). Moreover, a study showed that written expression skills affect academic performance in other areas much more than do the intensity of ADHD symptoms, comorbidity with oppositional defiant disorder, use of medication, reading ability, and intelligence (Molitor, Langberg, & Evans, 2016b).…”
Section: Introductionmentioning
confidence: 95%
“…The low quality of texts produced by ADHD students (Re et al, 2007;Re & Cornoldi, 2010;Kim et al, 2013;Miranda et al, 2011), the high prevalence of this disorder in childhood and adolescence (Polanczyk, Lima, Horta, Biederman, & Rohde, 2007), and the scarcity of publications on the topic underscore the clear need for further research on the development and implementation of interventions designed to facilitate the writing processes of students with this disorder (Miranda et al, 2013;Semrud-Clikeman, 2012;Molitor et al, 2016b). In this context, the question is: what interventions can contribute to improving the writing performance of students with ADHD?…”
Section: Introductionmentioning
confidence: 99%